Microtus hyperboreus (Mammalia, Rodentia) в юго-восточной Якутии - Боескоров, Г.Г.; Егоров, Н.Г.; Ревин, Ю.В. (Вестник зоологии, 1993)
Karyological evidence of a middendorfii group vole representative occurrcnce in south-eastern Yakutia (lower Maya river), i. e. in an area formerly not included in their range. Chromosomal set of 2 examined females consists of 50 chromosomes, inorphologilally identical to the described Middendorf’s vole karyotype Range and habitat distribution data support their identification as M. Iiyperboreus.